Manipulating Levels of Socially Evaluative Threat and the Impact on Anticipatory Stress Reactivity - Craw, Olivia A.; Smith, Michael A.; Wetherell, Mark A. (Frontiers in Psychology, 2021)
Previous work suggests that relative increases in socially evaluative threat modulate the psychobiological stress response. However, few studies have compared stressors which manipulate the level of socially evaluative threat to which the participant is exposed. Here we present two studies. In the first, we assessed the integrity of an ecologically valid, laboratory stressor (direct socially evaluated multitasking) and its effects on acute psychobiological reactivity and ability to evoke an anticipatory response prior to participation. Specifically, we assessed whether the expectation and experience of direct social evaluation (multitasking while standing and facing an evaluator) evokes greater reactivity than indirect evaluation (over-the-shoulder evaluation). In the second study, we sought to replicate the findings regarding acute stress reactivity whilst extending the assessment window to assess the extent to which the stressor evokes anticipatory responses. As hypothesized, greater reactivity was observed following direct social evaluation compared with indirect observation. Increases in anxiety, heart rate and blood pressure were demonstrated across both studies and the paradigm therefore provides an ecologically valid technique for the activation of psychological and cardiovascular stress responding. Additionally, anticipation of experiencing socially evaluated multitasking led to increases in anxiety, tension, and worry prior to the event itself, supporting previous suggestions that threat anticipation may prolong the activation of stress mechanisms. In the present studies we assessed whether the expectation and experience of direct social evaluation evokes greater reactivity than indirect evaluation. The findings have demonstrated that direct social evaluation of multitasking is a more potent stressor than multitasking with indirect evaluation. Furthermore, our findings indicate that the period of anticipation of stressful events may be critical to understanding the process of stress regulation, and as such we recommend extending the sampling window to allow for the investigation of these processes.